EVALUASI PENGGUNAAN OBAT TUKAK LAMBUNG PADA PASIEN RAWAT JALAN DI RUMAH SAKIT EFARINA ETAHAM KOTA PEMATANGSIANTAR PERIODE JANUARI- MARET TAHUN 2024 - Emi Sugesti; Meyana Marbun, Hekdin Marsius Sipayung, Devi Yuliani Luming (CV. Adiba Aisha Amira, 2025)
Gastric ulcers are a condition where there is injury to the esophageal area, the lining of the stomach or duodenum caused by Helicobacteri pylori bacteria. Gastric ulcers can be caused by several factors, namely smoking, fast food, alcoholic drinks, NSAIDs and Helicobacteri pylori.The aim of this research is to determine the characteristics of the drugs used and the rationale for drug use in gastric ulcer patients. This research uses a descriptive method with a research design where data collection is carried out retrospectively, namely by searching the treatment records of gastric ulcer patients contained in prescription data or records. medical in the outpatient installation of Efarina Etaham Hospital, Pematangsiantar City for the period January-March 2024.he sample used was 75 prescriptions that met the inclusion criteria, based on research results, the types of drugs used for gastric ulcer patients were Lansoprazole 74.6%, Omeprazole 14.6%, Sucralfate 46.6%, Domperidone 20%, Antacids 1.3 %. The results of the rationality evaluation obtained 100% correct patient, 100% correct drug dose, 100% correct indication, 100% correct drug selection, 100% correct duration of administration. Overall, treatment that meets the 5 rationalities of rational treatment is 100%.